PECULIARITIES OF ETYMOLOGY AND LEXICAL STRUCTURE OF ENGLISH BRAND NAMES OF DISHES - Lyssenko , Catherine (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article considers such aspects of modern English vocabulary as the names of culinary dishes, food consumption and the history of their names. In modern conditions of intercultural communication the formation, strengthening of intercultural relations, specific features of each language come to the fore. Food itself is one of the main manifestations of cultural relationships today. That is why the study of various aspects of gastronomic discourse, which are influenced by different national cuisines in our rapidly changing modern world, is gaining new impetus. Under the gastronomic discourse in our work we understand a special kind of verbal and social discourse, the purpose of which is to achieve a certain type of communication. It is a piece of text or language related to the eating process in which the participants are considered, the conditions, the ways of communication, the environment in which the conversation takes place. In modern conditions of intercultural communication, the formation, strengthening of intercultural relations, specific features of each gastronomic preference have been formed over the centuries, and, of course, features such as geographical location, climate, religion, traditions and foundations, as well as economic factors could not affect them. . It is often enough to just look at what a person eats to determine where he comes from, what beliefs he has and what lifestyle he leads. It is known that the linguistic personality exists in a certain culture and has basic values – cultural concepts. The concepts that exist in the collective consciousness are essential for both the individual and for collective cultural identity in general. The problem of defining the concept of "food" as a cultural concept in modern language theory in the 21st century is of great interest to linguists and linguistic and cultural scientists. This concept in linguistic culture is one of the least studied and defined, although its meanings and cultural values ​​are quite high. The food and cuisine of any nation are integral to the language and are reflected in its vocabulary. In the system of national values, the cultural concept of "food" occupies one of the key places. This phenomenon can be viewed from different angles. ____________ REFERENCES • Belenko, E. V. «Konceptosfera «Produkty pitanija» v nacional’noj jazykovoj kartine mira.» [Conceptosphere “Food stuff” in the national language picture of the world”] (Diss. kand. filol. nauk, Cheljabinsk, 2006), 243. • Vezhbickaja, A. Kul’tura. Poznanie [Language. Culture. Knowledge] (Moskva, Russkie slovari, 1996), 416. • Marushkina, N. S. «Gastronomicheskie» frazeologicheskie edinicy kak sredstvo formirovanija koncepta Eda.» [“Gastronomic” phraseological units as a means of forming a concept “Food”] Prepodavatel’ XXI vek 2.2 (2012): 355–358. • Oljanich, A. V. «Prezentacionnaja teorija diskursa.» [‘Presentational theory of discourse”] Avtoref. doktora filol. nauk, Volgograd, 2004. • Anderson, Jay A. «Scholarship on contemporary American folk foodways.» Ethnologia Europaea: Revue Internationale d’Ethnologie Europeenne 5 (1971): 56–62. • Brillat-Savarin, Jean Anthelme. The Physiology of Taste, or, Meditations on Transcendental Gastronomy (Washington DC, Counterpoint, 1994). • Cakes and pastries, 11th edition, by Cleve Carney (Chicago, 1926). • Inness, Sherrie A. Pilaf, Pozole, and Pad Thai: American Women and Ethnic Food (Amherst, University of Massachusetts, 2001). • Old-fashioned cookery book compiled, by the Market bulletin (East Charleston, WV 25305), agriculture.wv.gov. • Peckham, Shannan. «Consuming nations.» Consuming Passions: Food in the Age of Anxiety, eds. Sian Griffiths & Jennifer Wallace (Manchester, Manchester University Press, 1998): 171–203. • The VJJE Recipe Weekly Archives 2000 Potpourri Recipes, www.e-cookbooks.net • White Stokes. Book of candy formulas (Chicago, 1917).